Arguments for the Existence of God in the Francisco Suarez’ "Metaphysical Disputations" - Vdovina, Galina (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2017)
The article considers arguments for the existence of God that are presented in Francisco Suarez’ treatise Metaphysical Disputations. The work of Suarez contains the most developed and detailed exposition of natural theology that exists in the scholastic tradition. Suarez explicitates the problem, formulating three questions: what is a being that we call God? Is it possible to prove or justify his existence? How is it possible? Suarez answers the first question by showing that we come to a concept of the prime and excellent being through a series of divisions in the concept of being. That prime being is infinite, absolute, necessary and uncreated. The second question is answered by the procedure of that division and its result. In his answer to the third question, Suarez distinguishes physical and metaphysical arguments. According to Suarez, the most significant physical proofs are the argument from motion and the argument from the rational soul. Nevertheless, he demonstrates that purely physical arguments cannot lead us to a being, which we call God. Only metaphysical argument from the principle, everything which is produced, is produces by something else, is really effective. The logic of the metaphysical proof is as follows: first, we have to demonstrate the necessary existence of the first non-produced thing: secondly, we are to show that such a thing can only be one. The first point is proved through the demonstration of an absolutely first cause in each series of causes, the second one is made evident through a demonstration of the impossibility to coexist simultaneously for two equally perfect first causes of equal causing power.